The Relationship between Secondary School Students' Use of Metacognitive Reading Strategies and their Reading Achievement - Elfinesh Berhe G/hiwot; Alamirew G/Mariam G/Micheal (Journal of Modern Research in English Language Studies)
This study aimed to investigate how the reading abilities of ninth-grade Ethiopian students were related to their use of metacognitive reading strategies. A mixed-methods design was employed, incorporating datagathering instruments such as the reading comprehension part of Test of English as a Foreign Language (TOEFL), the Metacognitive Reading Strategies Inventory (MARSI), and semi-structured interviews. One hundred and fifty students (68 men and 82 women) took part in the reading test and filled out the questionnaire. Among them, six students were interviewed. The findings indicated a significant relationship between the utilization of metacognitive reading strategies by ninth-grade Ethiopian students and their reading proficiency, displaying a moderate level of correlation. The utilization of global and problem-solving reading strategies by students showed a significant correlation with their reading performance, whereas no correlation was detected between students’ use of reading support strategies and their reading performance. Regarding strategy preferences, the research revealed that high and medium achievers predominantly employed problem-solving strategies, followed by global and support strategies. On the other hand, low-achieving students used global reading strategies relatively more frequently, followed by support and problem-solving strategies. The qualitative data also corroborated the quantitative findings, revealing that high achievers demonstrated a more advanced understanding of metacognitive reading strategies, particularly problem-solving and global strategies, than did low and medium achievers. Similarly, medium achievers showed a better understanding of these strategies than low achievers.